Making “Si Mbah” Illustrational Asset for Whatsapp Stickers Need Using MDLC Method - Risqi Dwiarto; Argiyan Dwi Pritama; Ilham Albana (Universitas Amikom Purwokerto, 2023)
The rapid development of technology in the current era of globalization has brought many advances in various social aspects. The popularity of mobile devices as a means of communication has increased in recent years due to their high mobility. Currently, there are many applications Messenger which has spread to the general public using messaging applications to send messages in the form of text, audio, and even files and videos. Verbal communication when chatting is prone to emotional misinterpretation, not infrequently a joke is interpreted as something serious so that miscommunication occurs. Not infrequently misunderstandings like this will have an impact on tenuous relationships and feelings of discomfort. Using informative and attractive visual media can definitely make people read carefully and understand the audience better. Thus it can be concluded that the use of animated visual media labels with the MDLC method can make it easier for the audience to receive information that is clearer and easier to understand.